ChemInform Abstract: Recent Applications of Phosphane‐based Palladium Catalysts in Suzuki‐Miyaura Reactions Involved in Total Syntheses of Natural Products. Issue 18 (April 2016) - Rossi, Renzo; Bellina, Fabio; Lessi, Marco; Manzini, Chiara; Marianetti, Giulia; Perego, Luca A.
Abstract: Review: 805 refs.